JOACHIM LELEWEL AS CREATOR OF BOOK SCIENCE AND OF SOME OTHER SCIENCES OF COMMUNICATION AND INFORMATION IN LITHUANIA - NAVICKIENĖ, AUŠRA (Knygotyra, 2013)
The first three decades of the nineteenth century is an exclusive period of Vilnius University and Lithuanian science history, when there had been made a tremendous progress under the influence of general rise of science and culture throughout Europe during the Age of Enlightenment. At that time Vilnius university was famous both for its schools of Medicine, Natural and Exact Sciences, and for the School of Humanities – Vilnius Philosophical School, Vilnius Theological School, Vilnius Philological School, together with creators of modern history and scientists who began investigating phenomena of communication and information (i.e. history of book and book sector related subjects, libraries and their activity, book’s description). Professor J. Lelewel’s two-volume work “Two bibliographic books”, which had been printed in Vilnius (1823–1826), became a significant monument of nineteenth century science and contributed to development of book science and other traditional communication and information sciences not only in Lithuania, Poland, but also in other Eastern and Central European countries. After performing content and theoretical part analysis, defining the main issues and their relation with today’s classification of Communication and Information sciences, assembling a scholarly image of science that J. Lelewel referred as bibliography (i. e. proving answers to such questions as how did J. Lelewel name the new science, how did he understand its structure, main problems, and links to other sciences), it is concluded that J. Lelewel is not only a father of book science, bibliography, library science, codicology, and paleography, but also a creator of this prime science – science that is associated with origins of communication and information sciences in Lithuania.